Perbuatan Melawan Hukum (Onrechtmatige Daad) Menurut Pasal 1365 Kitab Undang-Undang Hukum Perdata dan Perkembangannya - Mendy Cevitra; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2023)
This research was conducted with the aim of knowing how to regulate the concept of unlawful acts and how the similarities and differences in default with unlawful acts. Using normative juridical research methods, it is concluded: 1. Unlawful acts (Onrechtmatigedaad) are a provision regulated in Article 1365 of the Civil Code that occurs a lot in society. Based on Article 1365 of the Civil Code, there are a number of elements, namely: 1. The existence of an act; 2. The act is against the law; 3. There is a mistake on the part of the perpetrator; 4. There is a loss to the victim; and 5. There is a causal relationship between actions and losses. 2. Legal acts have developed through jurisprudence both in the Netherlands and in Indonesia, which expands the meaning of legal acts not only violating the law, but also violating the decency and decency that live and prevail in society.